Measurement of angular asymmetries in the decays B[bar]→[kappa]∗l[iota]+l[iota]- - Lees, Jean-Pierre; Adametz, Aleksandra; Uwer, Ulrich (Physical review, 2016)
We study the lepton forward-backward asymmetry AFB and the longitudinal K∗ polarization FL, as well as an observable P2 derived from them, in the rare decays B→K∗ℓ+ℓ−, where ℓ+ℓ− is either e+e− or μ+μ−, using the full sample of 471 million B¯B events collected at the Υ(4S) resonance with the BABAR, detector at the PEP-II e+e− collider. We separately fit and report results for the K*0(892)ℓ+ℓ− and K*+(892)ℓ+ℓ− final states, as well as their combination K∗ℓ+ℓ−, in five disjoint dilepton mass-squared bins. An angular analysis of B+→K*+ℓ+ℓ− decays is presented here for the first time.